Estrategias didácticas para álgebra y funciones en segundo grado de educación general básica elemental - Mejía Condolo, María Fernanda (2017)
The didactic strategies are instruments for the teacher, and the teaching-learning process is closely linked to them. Therefore, the methodological proposal that governs this study is aimed at the design of methodological strategies to improve the teaching-learning process aimed at the learning of Mathematics in a creative, playful way and considering the methodological processes of mathematics. Hence it is considered as a problem of study: what kind of didactic strategies would favor the development of algebra and functions? After carrying out a previous study and finding that there was a deficit in the learning of the subject, it was decided to carry out this research, a reference sample was chosen and from it the research methods and techniques were applied that gave the possibility to enter In this study, the intention was centered on the fact that boys and girls recognize the Mathematics subject as a useful tool for their development and not as a subject that they need to overcome for the year. Then a proposal was made that consists of a theme, general and specific objectives, the problem to be addressed, the conceptual contents, the actions that will be carried out by the students and the teachers, the evaluation criteria and the timetable that indicates the time in which Will do the work. The technique used to construct the proposal was the observation to the students of Second Year of Basic.